Exploring support for shale gas extraction in the United Kingdom - Andersson-Hudson, Jessica; Knight, Wil; Humphrey, Mathew; O'Hara, Sarah (Elsevier, 2016)
The development of shale gas in the United Kingdom (UK) using hydraulic fracturing, more commonly known as ‘fracking’, remains in its infancy. Yet understanding public attitudes for this fledgling industry is important for future policy considerations, decision-making and for industry stakeholders. This study uses data collected from the University of Nottingham UK nationwide online survey (n=3,823) conducted in September 2014, to consider ten hypothesises about the UK public’s attitudes towards shale gas. From the survey data we can see that 43.11% of respondents support shale gas extraction in the UK. Furthermore, our results show that women, class DE respondents, non-Conservative party supporters, and respondents who positively associate shale gas with water contamination or earthquakes are less likely to support the extraction of shale gas in the UK. We also discuss potential policy implications for the UK government arising from these findings.